Towards developing a sustainability integration framework for building project - Isa, N.K.M.; Alias, A.; Samad, Z.A. (Penerbit UKM, 2014)
Sustainable building projects are naturally different from conventional projects due to the requirement of special materials and building practices, as well as the management commitment to sustainability. Therefore, a sustainable building project requires additional considerations on many aspects more than the conventional project. Although there are many researches on the paybacks of a sustainable building, nevertheless, huge numbers of barriers also contributes to the multiple failing of the projects within the market such as knowledge gaps, communication shortfall, ownership structure and operating cost responsibility, funding issues and the risks, and other technical and process issues. Many researchers believe that project planning process holds the strategic position in overcoming the barriers all together. Modifications should be made to the traditional planning process and practices in order to minimize risks and improve the chances of delivering the project successfully. This paper offers ideas and recommendations on the initial concept of sustainability integration strategies that can be practiced throughout the project planning process towards delivering a successful performance of a sustainable building. The concept is very useful to be a starting point for the development of a practical ‘Sustainability Integration Framework’ during the planning process of a sustainable building project in the future.